Leadership, violent conflict and reconciliation in Africa: : The theological-sociocultural engagement of Luke's Gospel in social transformation - Agbiji, Obaji M; Etukumana, Godwin (Stellenbosch Theological Journal, 2018)
This article considers anew the important role of leadership in a meliorating violent conflict and achieving reconciliation in African societies, using the Lukan Jesus' model of subversive leadership. The article critically engages Luke's narrative of Jesus' leadership style in achieving reconciliation in the context of violent conflict by using theological-sociocultural hermeneutical lenses. The Lukan Jesus, his leadership style and the manner in which he sought reconciliation in contexts of violent conflict offer African socio-political and religious leaders a model of effective leadership that could assist them in dealing with the social challenges Africa faces, such as poor leadership, violent conflicts and underdevelopment.